Gene expression patterns in Euglena gracilis: Insights into the cellular response to environmental stress - Dos Santos Ferreira, Veronica Beatriz (2007)
To better understand Euglena gracilis gene expression under different stress conditions (Chromium, Streptomycin or darkness), we undertook a survey of the E. gracilis transcriptome by cDNA sequencing and microarray analysis. First, we constructed a non-normalized cDNA library from the E. gracilis UTEX strain and sequenced a total of 1000 cDNAs. Six hundred and ten of these ESTs were similar to either Plantae or Protistae genes (e-value < e- 10). Second, microarrays were built by spotting all the ESTs onto mirror slides. Microarray expression analysis indicated that 90 out of those 610 ESTs changed their expression level in response to different stress treatments (p < 0.05). In addition, we detected 10 ESTs that changed expression levels irrespective of the tested stress. These may be considered as part of a larger set of stress-related genes in E. gracilis. Finally, we identified 23 unknown ESTs (U-ESTs) following the expression profiles of these putative stress-related genes suggesting that they could be related to the cellular mechanism of stress response.